Aplicação de silicato de potássio e crescimento foliar da cana-de-açúcar - Moraes, Wanderson B.; Jesus Júnior., Waldir C. de; Moraes, Willian B. [UNESP]; Araujo, Glaúcio L.; De Souza, Antonio F.; Da Silva, Márcia V. (Revista Brasileira de Ciencias Agrarias, 2011)
The objective of this study was to evaluate the effect of increasing doses of potassium silicate on the leaf growth of sugarcane under controlled conditions. The experiment was conducted in a completely randomized design, with six replications and six treatments consisting of doses of potassium silicate (0, 40, 80, 160, 200 and 240 g L -1). The leaf application of potassium silicate quadratically increased the leaf growth of sugarcane. The maximum growth of the leaf area and dry matter production of leaves were obtained with doses of 66.6 and 40.0 g L -1 of potassium silicate, respectively. With a dose of 51.0 g L -1 of potassium silicate, the maximum estimated value of leaf area ratio was obtained. The content of potassium (K) present in the dry matter of the leaf +1 responded linearly to the doses of potassium silicate. However, the high concentration of K in function of the application of high doses of potassium silicate reduced the leaf growth of sugarcane. Therefore, to obtain the maximum leaf growth of sugarcane the dose of potassium silicate to be applied should be between 40.0 and 66.6 gL -1.
Application of potassium silicate and leaf growth of sugarcane
Keywords: Leaf fertilization; Mineral nutrition; Saccharum spp.; Silicon; Saccharum